Chapter Tempo e aspetto nella narrazione in ceco in una prospettiva diacronica - ESVAN, Francois Jean (Biblioteca di Studi Slavistici, 2016)
Regarding the historical present in Czech narrative the author proposes to distinguish three main modes: (i) the narrative present, which follows the same aspectual opposition system of the past tense narration mode; (ii) the tabular present, which neutralizes the aspectual opposition in favour of the imperfective aspect; (iii) the complementary distribution, which alternates past perfective and present imperfective. This assumption allows to reconsider the hypothesis of a trend to neutralize aspectual opposition in the historical present in Czech (Bondarko 1958).